Analisa Perhitungan Nilai Kapsitor Bank untuk Perbaikan Faktor Daya pada PT. Karya Toha Putra - Lestari, Putri Dwi; Gunawan, Gunawan; Widihastuti, Ida (Elektrika, 2020)
The use of electricity with large capacity sometimes faces various kinds of problems. These problems include network losses and voltage drops that occur in the channel. Improvement of electric power factor at PT. Karya Toha Putra is expected to improve the quality of electric power. This improvement is also expected to reduce the cost of electricity bills at PT. Karya Toha Putra. To be able to implement improvements in the quality of the electric power, it is necessary to calculate the reactive power compensated. In this case the power factor to be achieved is 0.95. After doing these calculations, the determination of the capacitor value will be used. By doing these stages, it is expected that the installation of capacitor banks can improve the quality of electric power. Bank capacitors are collections of capacitors used to provide reactive power compensation to improve the electrical power factor. From the results of the study showed that the amount of compensation needed to improve the power factor at PT. Karya Toha Putra is 50 kVAR, divided into 5 steps with one step, a capacitor of 10 kVAR.